The official history of criminal justice in England and Wales: volume V, policing post-war Britain : plus ça change - Newburn, Tim (Government official history series, 2024)
Misconduct, scandal and growing scrutiny -- The Royal Commission -- Towards the Police Act -- Conduct and complaints -- The police and Criminal Evidence Act -- Malpractice and another Royal Commission -- Early organisational change -- The rise and fall of unit beat policing -- Community policing -- Crime prevention -- Race, racism and policing -- Women and policing -- The tide turns -- Urban unrest -- Enter Lord Scarman -- The miners' strike -- Rioting returns -- Policing under the spotlight -- A changing political context -- Police finance and efficiency -- The rise of managerialism and consumerism -- Reform attempts gather pace -- The limits of fundamental reform.